A template Bayesian network for combining forensic evidence on an item with an uncertain relation to the disputed activities - M. Vink; J.A. de Koeijer; M.J. Sjerps (Forensic Science International: Synergy)
Most of the forensic evidence evaluations given activity level propositions are centered around an item which is assumed to be linked to an alleged activity. However, the relation between an item of interest and an activity may be contested. This study presents a template Bayesian network (BN) for the evaluation of transfer evidence given activity level propositions considering a dispute about the relation of an item to one or more activities. The template BN includes a set of association propositions that enables the combined evaluation of evidence concerning alleged activities of the suspect and evidence concerning the use of an alleged item in those activities. Since the two types of evidence are often from different forensic disciplines, the BN is especially useful in interdisciplinary casework. Throughout the paper, we use a fictive case example that captures the essence of cases for which the template model can be used. The template BN provides a flexible starting point that can be adapted to specific case situations and supports structured probabilistic reasoning by a forensic scientist.